2021
DOI: 10.21203/rs.3.rs-668716/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catechol, a Natural Allelochemical Thwarts Virulent Dimorphism in Candida Albicans and Potentiates the Antifungal Efficacy of Azoles and Polyenes.

Abstract: The present study was deliberately focused to explore the antivirulence efficacy of a plant allelochemical –catechol against Candida albicans, and attempts were made to elucidate the underlying mechanisms as well. Catechol at its sub-MIC concentrations (2 to 256 μg/mL) exhibited a dose dependent biofilm as well as hyphal inhibitory efficacies, which were ascertained through both light and fluorescence microscopic analyses. Further, sub-MICs of catechol displayed remarkable antivirulence efficacy, as it substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Catechol, while unable to inhibit Candida itself, potentiates the antifungal activity of azoles and polyenes, and prevents up-regulation of virulence-associated genes. Curiously, catechol did not reduce the viability of Candida biofilms, but did reduce their hydrophobicity [300].…”
Section: Azole Synergy With Natural Productsmentioning
confidence: 93%
“…Catechol, while unable to inhibit Candida itself, potentiates the antifungal activity of azoles and polyenes, and prevents up-regulation of virulence-associated genes. Curiously, catechol did not reduce the viability of Candida biofilms, but did reduce their hydrophobicity [300].…”
Section: Azole Synergy With Natural Productsmentioning
confidence: 93%
“…For the fluorescence microscopy, a live-dead stain assay was performed by following previously described protocol by Ravi et al 27 . The slides were washed with sterile PBS, stained with 0.1% of acridine orange (AO) and ethidium bromide (EtBr) (1:1) (Sigma Aldrich) under dark conditions for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Catechol, when applied in concentrations of 2–256 μg/mL, could dose-dependently inhibit biofilm and hyphal formation of C. albicans , it also inhibited virulence factors secreted hydrolases and reduced EPS levels in biofilm matrix. The qPCR data indicated that catechol application induces significant down-regulation of RAS1 , HWP1, and ALS3 , genes linked with the fungal pathogenesis [ 69 ].…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%